Socioeconomic Factors and Its Correlation with Nutritional Status in Toddlers: A Study in Papua - Anita Ratna Etnis; Wahyuni Maria Prasetyo Hutomo; Hansen Maikel Su; Irfandi Rahman; Endofita Kolong (Journal of Health Sciences and Epidemiology, 2024)
Nutritional status in toddlers is a critical indicator of overall well-being and long-term health outcomes. Malnutrition among children is persistent and continues to be an alarming burden, often linked to socioeconomic factors in Papua. This study aims to analyze the relationship between socioeconomics and the nutritional health of toddlers. This cross-sectional study involved 300 toddlers aged 1–5 years from working areas at the Primary Health Center (PHC) Remu, Sorong City, Papua. We collected data by conducting structured interviews with the mothers and measuring the anthropometric traits of the toddlers. Socioeconomics was assessed through family income, maternal education, and access to healthcare. We measured nutritional status using WHO standards for weight-for-age (underweight), height-for-age (stunting), and weight-for-height (wasting). We implemented the Pearson and Spearman correlation tests for data analysis. The results indicated family income (p < 0.05), maternal education (p < 0.05), and access to healthcare (p < 0.05) were significantly correlated with nutritional status. This study highlights the significant influence of socioeconomic status on the nutritional status of toddlers in Papua. Toddlers from families with higher income, better maternal education, and enhanced accessibility to healthcare had better nutritional outcomes, with lower rates of stunting, wasting, and underweight. These findings suggest the need for targeted interventions aimed at improving socioeconomic conditions and enhancing access to nutritional and healthcare services in Papua, particularly in rural and remote areas, to reduce malnutrition and promote better health outcomes for children.